USES OF QUALITATIVE RESEARCH IN HEALTH. IS THERE SOMETHING BEYOND THE DISSEMINATION OF RESULTS? - Mercado Martínez, Francisco Javier; Robles Silva, Leticia (Investigación y Educación en Enfermería, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The aim of this paper is to examine the dissemination and use of qualitative health research. The paper is divided into two parts. In the first part, three common approaches are identified regarding the use and application of research results: one is interested in the dissemination of knowledge to academia; another looks at the knowledge transfer and translation to strengthenhealth policies and programs; and the last one is geared towards the population. The second part presents a relational and dialogic proposal for the transfer and use of qualitative research in the health area in the context of the Latin American countries.